Meteorus cis - Stigenberg, Julia; Ronquist, Fredrik (Zenodo, 2011)
Meteorus cis (Bouché) Fig. 91 Bracon cis Bouché, 1834:149. Type material unknown. Perilitus profligator Haliday, 1835:33. Syntypes ♀ Ireland (lost). Synonymized by Fahringer 1928:505. Diagnosis : Meteorus cis is similar to M. breviantennatus but the clypeus of the latter is almost as wide as the face while the clypeus of M. cis is narrow. Also the malar space (shorter than mandibular base on M. breviantennatus , as wide as mandibular base on M. cis ) and the face (slightly more transverse face in M. brevianennatus , round face in M. cis ) should separate these species. Studied material : ~ 20 specimens. Description : Size about 2.5–3.5mm. Antennae 20–22 articles. Head rounded behind eyes. Ocelli small, OOL=3. Eyes small, not strongly protuberant, slightly convergent. Malar space slightly shorter than basal breadth of mandible. Face 1.5–2.0 times as broad as high, smooth, punctate, not strongly protuberant. Clypeus narrower than face, almost flat, its apical border weakly notched medially and usually with a weak vertical impression behind the notch. Tentorial pits distinct. Mandibles short, stout and moderately twisted. Precoxal sulcus foveolate, sometimes broadening anteriorly. Mesopleuron dorsally reticulate-rugose, otherwise smoothly punctate. Propodeum with carinae with very weak rugose sculpture in between. Petiolar tergum with large distinct dorsal pits, dorsal surface generally reticulate-rugose with a few longitudinal striae laterally. Ovipositor about twice the length of petiolar tergum, slender. Legs slender; hind coxa never strongly rugose but often with a trace of obsolescent rugosity at the base and on the outer surface. Tarsal claws not lobed but somewhat swollen basally. Colour testaceous to brown; clypeus, mandibles and usually 3 rd abdominal tergite reddish testaceous; coxa and legs yellow. Pterostigma dark with light border around, more so anteriorly. Fore wing m-cu antefurcal, vein 2-SR+M almost as long as vein r, at most 0.7 times). Distribution : Palearctic. Country records: Austria; China; France; Germany; Ireland; Japan; Korea; Netherlands; Sweden; United Kingdom. Biology : Meteorus cis is recorded as a parasitoid of Cis boleti Scopoli, 1763 (Bouché 1834). We found 12 specimens within the SMTP; they were caught in both deciduous and coniferous forests. Flying time is from July to October. : Published as part of Stigenberg, Julia & Ronquist, Fredrik, 2011, Revision of the Western Palearctic Meteorini (Hymenoptera, Braconidae), with a molecular characterization of hidden Fennoscandian species diversity 3084, pp. 1-95 in Zootaxa 3084 (1) on page 50, DOI: 10.11646/zootaxa.3084.1.1, http://zenodo.org/record/5244448 : {"references": ["Bouche, P. F. (1834) Naturgeschichte der Insekten, besonders in Hinsicht ihrer ersten Zustande als Larven und Puppen. Lieferung 1. Berlin, Nicolai, 8 vo. v, 216 pp.", "Haliday, A. H. (1835) Essay on parasitic Hymenoptera. The Entomological magazine, 3, 20 - 45.", "Fahringer, J. (1928) Opuscula Braconologica. Band 1, Palaearktischen Region, 433 - 606 pp."]}